Acceptance and Attitudes Towards Covid-19 Vaccines Among Student and Staff in UTHM Pagoh - AWALUDDIN, NUR ALIA (Multidisciplinary Applied Research and Innovation, 2023)
COVID-19 vaccine has become important during the pandemic outbreak in 2019. It has been developed by researchers in a short period of time which then raises questions about its effectiveness among the Malaysian population. This technical paper is about the acceptance and attitudes towards Covid-19 vaccines among students and staff in Universiti Tun Hussein Onn (UTHM) Pagoh as there are some people who may be reluctant to take the COVID-19 vaccine. The main objective of this study is to find out the percentage of acceptance, evaluate the attitudes and measure the level of knowledge about COVID-19 vaccine among students and staff in UTHM Pagoh. A cross-sectional study of 273 respondents among students and staff of UTHM Pagoh was carried out through a questionnaire in a Google Form consisting of four sections. There is demographic, acceptance, attitude and level of knowledge toward COVID-19. The attitude section in this study focus on confidence, complacency and convenience of respondents toward COVID-19 vaccine. The questionnaire was distributed via WhatsApp and Gmail which then were analysed using SPSS software. The result of this study shows that the majority are willing to take the COVID-19 vaccine despite the fact that it has a less testing period compared to other vaccines. Their attitude toward vaccine confidence, importance, and satisfaction is also very positive. Also, they show high level of knowledge in COVID-19 vaccine. Hopefully, this study will be improved in the future based on scope of study and other factors that affect the confidence level among Malaysian populations.